2008
DOI: 10.1021/bi8007356
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystallographic and Solution State Nuclear Magnetic Resonance Spectroscopic Investigations of NADP+ Binding to Ferredoxin NADP Reductase from Pseudomonas aeruginosa,

Abstract: The ferredoxin nicotinamide adenine dinucleotide phosphate reductase from Pseudomonas aeruginosa (pa-FPR) in complex with NADP+ has been characterized by X-ray crystallography and in solution by NMR spectroscopy. The structure of the complex revealed that pa-FPR harbors a pre-formed NADP+ binding pocket where the cofactor binds with minimal structural perturbation of the enzyme. These findings were complemented by obtaining sequential backbone resonance assignments of this 29,518 kDa enzyme, which enabled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…It is likely that cross-peaks corresponding to Ser2 and Ser103 cannot be detected due to conformational disorder because Ser2 becomes the amino terminal residue upon cleavage of the initiator Met during expression in E. coli and Ser 103 is located in the loop exhibiting the highest B-factors in the X-ray crystal structure. Resonances originating from several of the remaining residues listed in Table 2 were assigned with the aid of samples selectively labeled with 15 N-Val, 15 N-Thr, 15 N-Leu, or 15 N-Tyr and 2D 1 H- 15 N HSQC experiments tailored to detect fast relaxing signals (37), in a manner similar to that used for the assignment of fast relaxing signals in heme oxygenase (18) and FPR (38) from Pseudomonas aeruginosa . For example, the HSQC spectrum of 15 N-Val HasAp acquired with standard conditions (Figure 6-A) displays 8 cross-peaks corresponding to previously assigned Val residues.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that cross-peaks corresponding to Ser2 and Ser103 cannot be detected due to conformational disorder because Ser2 becomes the amino terminal residue upon cleavage of the initiator Met during expression in E. coli and Ser 103 is located in the loop exhibiting the highest B-factors in the X-ray crystal structure. Resonances originating from several of the remaining residues listed in Table 2 were assigned with the aid of samples selectively labeled with 15 N-Val, 15 N-Thr, 15 N-Leu, or 15 N-Tyr and 2D 1 H- 15 N HSQC experiments tailored to detect fast relaxing signals (37), in a manner similar to that used for the assignment of fast relaxing signals in heme oxygenase (18) and FPR (38) from Pseudomonas aeruginosa . For example, the HSQC spectrum of 15 N-Val HasAp acquired with standard conditions (Figure 6-A) displays 8 cross-peaks corresponding to previously assigned Val residues.…”
Section: Resultsmentioning
confidence: 99%
“…Samples selectively labeled with 15 N-Gly, 15 N-Ala, or 15 N-Val were prepared with the above-described protocols supplementing the M9 media according to previously reported procedures 2123…”
Section: Experimental Methodsmentioning
confidence: 99%
“…104 Nuclear magnetic resonance (NMR) spectroscopic and X-ray crystallographic studies conducted with Pa FPR showed, for the first time, the interactions between a bacterial FPR and NADP + ; the cofactor binds to a preformed binding site on the structure of Pa FPR and the complex is stabilized by interactions between the protein and the 2′P AMP portion of the cofactor. 107 Prior to the structural characterization of the Ftn-like molecules in P. aeruginosa, 64,67 it was thought that the bacterium harbored a Bfr assembled from two distinct types of subunits, termed α and β 108 Studies carried out in 1999 demonstrated the presence of two genes encoding Ftn-like molecules in P. aeruginosa, which were named bacterioferritin A (bfrA) and bfrB. 109 The authors also showed that P. aeruginosa mutants lacking the bfrA gene express 50% of the catalase activity of the wild-type cell but that full catalase activity could be rescued by complementation with a plasmid expressing the bfrA gene.…”
Section: A Protein-protein Interactions Regulate the Release Of Ironmentioning
confidence: 99%